Comparative Study on the Field- and Lab-Based Soil-Water Characteristic Curves for Expansive Soils. (2nd May 2022) - Zamin, Bakht; Nasir, Hassan; Sikandar, Muhammad Ali; Ahmad, Waqas; Khan, Beenish Jehan; Ahmad, Mahmood; Bashir, Muhammad Tariq
Abstract : Expansive soils are problematic and viewed as a potential hazard for buildings and structures due to swell and shrink phenomena. The damaging effect of these soils is strongly correlated with the soil-water characteristics of expansive soils present in the shallow depth. The seasonal wetting-drying cycle is vital in fluctuating moisture content in the surficial soils. As such, soils remain unsaturated most of the time due to high absorption capacity. Therefore, it is crucial to assess them as unsaturated soil, and the soil-water characteristic curve (SWCC) is an essential tool for measuring unsaturated soils' mechanical and hydraulic properties. The main objective of this study was to establish both field- and lab-based SWCCs for the expansive soils and compare them for determining the possible difference between them. For this purpose, eight sites of expansive soils were selected for sampling and in situ testing. These sites include three locations of Karak, three locations of Kohat, and two locations of D.I areas. Based on the experimental results, Karak's expansive soil indicated a high suction value of 705 kPa, while D. I Khan's soil showed the least suction equal to 595 kPa. The comparison of field and lab SWCCs for the potential sites presented a close agreement in the matric suction values beyond the air entry values (AEVs), particularly in the residual suction zones. It was also concluded that for expansive soils, the field- and lab-based SWCCs are comparable beyond the AEVs. The established curves can be successfully utilized to assess local expansive soils in the framework of unsaturated soils.